A Case of Ductal Carcinoma In Situ(DCIS)Diagnosed by Excisional Biopsy with Benign Cytology Findings of Fine-Needle Aspiration - Ishizuka, Mariko; Yamamoto, Daigo; Shoji, Tetsuji; Sueoka, Noriko; Miyata, Mami; Umezaki, Nodoka; Yoshikawa, Katsuhiro; Yoshida, Nao; Sekimoto, Hirotsugu (Gan to kagaku ryoho, 2019)
Nipple discharge is a common symptom and frequently results from benign tumors. However, there is a 5-30% risk of malignancy. A 65-year-old woman presented at the hospital because of bloody nipple discharge in her right breast. She had noticed an abnormal nipple discharge for several months. Mammography showed focal asymmetric densities without calcification in the middle outer quadrant of her right breast. Ultrasonography indicated a 1.5×1.1 cm sized cyst with fluid-fluid level. Breast MRI showed a simple cyst with a benign contrast enhancement pattern. No malignant cells were observed by fine-needle aspiration. Considering the low sensitivity of mammography and breast MRI to DCIS, we performed an excisional biopsy. Histological examination revealed that the lesion was DCIS. The patient underwent right total mastectomy and was diagnosed with low grade DCIS(ER-positive, PgR-positive, HER2-negative). She continues endocrine therapy with an aromatase inhibitor.